2000
DOI: 10.1074/jbc.275.13.9792
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Tyrosine Phosphatases That Dephosphorylate the Insulin Receptor

Abstract: Many pharmacologically important receptors, including all cytokine receptors, signal via tyrosine (auto) phosphorylation, followed by resetting to their original state through the action of protein tyrosine phosphatases (PTPs). Establishing the specificity of PTPs for receptor substrates is critical both for understanding how signaling is regulated and for the development of specific PTP inhibitors that act as ligand mimetics. We have set up a systematic approach for finding PTPs that are specific for a recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
98
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 159 publications
(100 citation statements)
references
References 36 publications
2
98
0
Order By: Relevance
“…Rat adipose cells overexpressing PTP␣ showed significantly lower insulin-stimulated levels of cell surface GLUT4 and a 3-fold decrease in insulin sensitivity (9). Although, in the first study (7), PTP␣ overexpression decreased insulin receptor Tyr phosphorylation, the demonstration that the insulin receptor is a substrate of PTP␣ has not been a consistent finding (8,10).…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Rat adipose cells overexpressing PTP␣ showed significantly lower insulin-stimulated levels of cell surface GLUT4 and a 3-fold decrease in insulin sensitivity (9). Although, in the first study (7), PTP␣ overexpression decreased insulin receptor Tyr phosphorylation, the demonstration that the insulin receptor is a substrate of PTP␣ has not been a consistent finding (8,10).…”
mentioning
confidence: 75%
“…Several studies have suggested that it acts as an inhibitor of insulin signaling (7,47,48), yet other reports have not confirmed these actions (8,10). We sought to investigate this hypothesis in skeletal muscle, a major insulin target tissue, and employed the rat skeletal muscle cell line L6.…”
Section: Discussionmentioning
confidence: 99%
“…The acute regulation of eNOS was monitored through association with HSP-90 and protein phosphorylation of T494, S632, and S1176. Finally, an in vitro model of insulin resistance was induced in endothelial cells via adenoviral expression of protein tyrosine phosphatase (PTP) 1B (51). Regardless of the model, eNOS expression, phosphorylation, or binding to HSP-90 was undiminished.…”
mentioning
confidence: 99%
“…18,19 Received Moreover, a recent study has shown that a related enzyme, PTP-PEST, has the capacity to dephosphorylate a tyrosinephosphorylated oligo peptide sequence based on the insulin receptor. 20 These findings prompted us to test the hypothesis that NO inhibits the cell motility-stimulatory effect of insulin in aortic smooth muscle cells via a mechanism mediated by PTP1B and/or PTP-PEST. We now report that PTP1B is necessary and sufficient to account for the capacity of NO to attenuate insulin-stimulated cell motility.…”
mentioning
confidence: 99%